2020
DOI: 10.1177/0961203320969976
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of anti-DFS70 antibodies prolonged survival of lupus-prone mice

Abstract: Background Systemic-lupus-nephritis is a chronic autoimmune disease characterized by immune complex deposition and a flare of autoantibodies and leading to renal injury. Objectives To expose anti-Dense-Fine-Speckled-70 (DFS70)-antibodies to genetically-prone-lupus-mice. Methods NZBXW/F1 female mice were monitored for the onset of glomerulonephritis by proteinuria upon infusion of anti-DFS70 (40 μg/mouse), commercial-human-IgG (cIgG) or phosphate-buffered-saline (PBS) as controls. The survival time was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
7
1
1
Order By: Relevance
“…Although the treatment strategies (Supplemental Table 1) and disease duration of our LN and NLN-SLE patients were different, which was almost inevitable in clinical settings, a similar prevalence of anti-DFS70 antibodies in our newly onset LN and NLN-SLE patients was also be observed. Murine studies have demonstrated the protective effects of anti-DFS70 antibodies purified from HI in attenuating LN development in lupus-prone mice (11). However, our clinical observations do not support the protective role of anti-DFS70 antibodies in SLE patients.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Although the treatment strategies (Supplemental Table 1) and disease duration of our LN and NLN-SLE patients were different, which was almost inevitable in clinical settings, a similar prevalence of anti-DFS70 antibodies in our newly onset LN and NLN-SLE patients was also be observed. Murine studies have demonstrated the protective effects of anti-DFS70 antibodies purified from HI in attenuating LN development in lupus-prone mice (11). However, our clinical observations do not support the protective role of anti-DFS70 antibodies in SLE patients.…”
Section: Discussioncontrasting
confidence: 78%
“…To date, no defined autoantibodies or clinical manifestations have been found to be associated with anti-DFS70 antibodies (7). In a recent paper, Aljadeff et al (11) reported that anti-DFS70 antibodies purified from HI tempered renal progression in lupus-prone mice. They inferred that anti-DFS70 antibodies potentially could protect against renal injury in SLE patients (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a hypothesis suggesting that anti-DFS70 are protective was previously considered. 5 In summary, the findings of Aldajeff et al in a murine model of SLE exposed to anti-DFS70 1 need further clarification but are nevertheless interesting and might be supported by earlier studies of human SLE. However, longitudinal studies are needed to clarify the longer-term importance or protective effects of anti-DFS70 in SLE.…”
mentioning
confidence: 80%
“…Sir, We read with great interest the recently published study by Aljadeff et al 1 reporting that weekly infusions of affinity-purified human anti-DFS70 antibodies into NZBxW/F1 mice resulted in improved survival rates, which might be attributed to the observation that 80% of the anti-DFS70 injected mice did not exhibit histological evidence of glomerulonephritis (GN). It is not clear if the remaining 20% had severe GN.…”
Section: Do Anti-dfs70 Antibodies Temper Disease Activity and Progresmentioning
confidence: 99%